An experimental study on two-phase flow patterns and heat transfer characteristics during boiling of R134a flowing through a multi-microchannel heat sink - Thiangtham, Phubate; Keepaiboon, Chanyoot; Kiatpachai, Parinya; Asirvatham, Lazarus Godson; Mahian, Omid; Dalkilic, Ahmet Selim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The present paper presents an experimental study of flow patterns and heat transfer characteristics of flow boiling of R134a in a multi-microchannel heat sink. The copper test section has 27 parallel rectangular channels with a depth of 470 mu m, a width of 382 mu m, a length of 40 mm, and a fin thickness of 416 mu m. The experimental results are presented for saturation temperatures of 13, 18, and 23 degrees C, and mass fluxes of 150, 400, and 600 kg/m(2) s. The wall heat flux and inlet vapor quality values were between 3 and 127 kW/m(2), and 0.05 and 0.92, respectively. The effects of pertinent parameters on the heat and fluid flow characteristics such as saturation temperature, mass flux, heat flux, and inlet vapor quality are studied and discussed. The heat transfer coefficient at high saturation temperatures (i.e. 23 degrees C) is higher than low saturation temperatures (i.e. 13 degrees C) in the heat flux range of 40-120 kW/m(2). For high heat flux ranges, the heat transfer coefficient increases with increasing mass flux. The convective boiling heat transfer mechanism will play a major role in wavy and annular flow patterns. For wall heat fluxes higher than 80 kW/m(2), the existence of a partial dry-out phenomenon in the multi-microchannel leads to a decrease in heat transfer coefficient. The results unveil the significant effect of flow patterns on heat transfer characteristics. Based on the experimental data, a correlation is proposed to calculate the heat transfer coefficient for R134a flow in the multi-microchannel heat sink that is useful in electronic cooling applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Flow boiling; Heat transfer; R134a; Micro-channel heat sink; REFRIGERATION COOLING APPLICATIONS; PRESSURE-DROP; FLUX; Thermodynamics; Engineering; Mechanics